Sources of Regional Banks Capitalization - Miroshnichenko, Olga Sergeevna; Tarasova, Anna Nikolaevna (Economy of Regions, 2018)
Searching of sources to increase the capitalization of Russian banks is an important economic problem for both the national and regional economy. Moreover, a strong capital base allows to credit institutions to meet the demands of economic agents for banking service. The research focuses on the choice of sources of regulatory capital for the banks of Tyumen region in the context of changing supervisory requirements in the period of2005-2016, in different phases of the business cycle. We apply econometric methods of statistical information using IBM SPSS Statistics software. We have calculated the individual correlations of regional banks' capital with gross domestic product (GDP) (excluding gross regional product (GRP)) and GRP (with the exception of the effect of GDP). These calculations have shown that the capital of regional banks is related only to GDP. The increase in the capital of regional banks is accompanied by a change in its structure: the share of authorized capital has halved, and the share of subordinated debt has grown. All sources of capital, other than the reserve fund, are related to GDP. Authorized capital is associated with the profit of profitable lending institutions; retained earnings in the capital of regional banks - with the aggregated amount of risks of the banking system of the Russian Federation. Subordinated debt, like capital as a whole, is negatively affected by the profitability of the banking sector. The change in the capital of regional banks is determined by the change in retained earnings, subordinated debt and reserve fund. Modelling of these relations has allowed to obtain a system of equations. This system synthesizes linear regression models of changing the capital of regional banks in the context of their sourcing. The results of this study are significant for theoretical justification and practical development of a balanced financial policy of regional banks. Our research will contribute to strengthening an adequate capital base as well as to the creation of a system of proportional bank regulation and supervision.